2021
DOI: 10.1155/2021/6663559
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Global Public Interest in the Internet Searches for Osteoporosis

Abstract: Background. To ascertain the seasonal pattern and global public interest in osteoporosis by evaluating search term popularity changes of the disease over a decade. Methods. We applied Google Trends to retrieve search popularity scores for the term “osteoporosis” between January 01, 2004, and December 31, 2019. Cosinor analyses were conducted to examine the seasonality of osteoporosis, and analysis on osteoporosis-related topics including hot topics and rising-related topics was also performed. Results. The cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…There were seasonal variations in the public interest regarding terms such as "running", "diet", "dietary supplements", "nutritionists", and "weight loss" [27] . Furthermore, searches for various diseases, including osteoporosis and skin diseases, demonstrated seasonality [28,29] . Research in the United States indicated a significant seasonal pattern in search intentions related to depression, with the lowest instances in summer and the highest in spring [30] .…”
Section: Identifying Environmental and Geographic Risk Factors Throug...mentioning
confidence: 99%
“…There were seasonal variations in the public interest regarding terms such as "running", "diet", "dietary supplements", "nutritionists", and "weight loss" [27] . Furthermore, searches for various diseases, including osteoporosis and skin diseases, demonstrated seasonality [28,29] . Research in the United States indicated a significant seasonal pattern in search intentions related to depression, with the lowest instances in summer and the highest in spring [30] .…”
Section: Identifying Environmental and Geographic Risk Factors Throug...mentioning
confidence: 99%